2004
DOI: 10.3748/wjg.v10.i14.2034
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancer-testis antigens in hepatocellular carcinoma

Abstract: CT antigens genes (MAGE-1, SSX-1, CTp11 and HCA587) are expressed with high percentage and specificity in HCC and their products are promising targets for antigen-specific immunotherapy of HCC. High frequent co-expression of multiple members of CT antigens in HCC provides possibility of polyvalent vaccinations for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Only 1 tissue out of 15 from the group of the PP tissues was very weakly positive; we explain this by influence of the tumour on normal tissue, which may take place in some cases. Such occurrences are well documented in the literature for mRNA/proteins for both CTA and non-CTA genes (Janz et al, 2002;Zhao et al, 2004).…”
Section: Discussionmentioning
confidence: 62%
“…Only 1 tissue out of 15 from the group of the PP tissues was very weakly positive; we explain this by influence of the tumour on normal tissue, which may take place in some cases. Such occurrences are well documented in the literature for mRNA/proteins for both CTA and non-CTA genes (Janz et al, 2002;Zhao et al, 2004).…”
Section: Discussionmentioning
confidence: 62%
“…Their selective normal tissue expression makes them ideal antigens for immune targeting of the malignant disease. In 2004, Zhao et al reported that of 105 HCC tissues, MAGE1, SSX-1, CTp11 and HCA587 mRNA expressions were detectable in 75.2%, 72.4%, 62.9%, and 56.2% of HCC samples, respectively [44]. About 93.3%, 72.4%, 48.6%, and 37.1% of HCC tissues positively expressed at least one, two, three, or four CT antigens, respectively.…”
Section: The Double Role Of the Cancer-testis Antigens Expression In mentioning
confidence: 98%
“…Moreover, some subjects exhibited increased amounts of CEA-specific CD8 C T lymphocytes coupled to decreased levels of CD4 C CD25 C FOXP3 C regulatory T cells (Tregs) after vaccination. 33 Butterfield and collaborators (University of Pittsburgh Cancer Institute, Pittsburgh, PA, USA) investigated the clinical profile of a prime-boost vaccination strategy relying on a pVAX1-based plasmid encoding full-length human a-fetoprotein (AFP), an oncofetal antigen frequently re-expressed by hepatocellular carcinoma (HCC), [98][99][100][101] co-injected i.m. with a granulocyte macrophage colony-stimulating factor (GM-CSF)-coding plasmid (prime), followed by a single intramuscular administration of an AFP-coding adenovirus (boost) (NCT00093548).…”
Section: 24mentioning
confidence: 99%